Research on the dynamic viseme of the lip shape based on facial motion capture technology - Zhu, Shengyin (Frontiers in Neurorobotics, 2022)
Abstract: In the study of articulatory phonetics, lip shape and tongue position are the focus of linguists. In order to reveal the physiological characteristics of the lip shape during pronunciation, the author takes the Tibetan Xiahe dialect as the research object and defines the facial parameter feature points of the speaker according to the MPEG-4 international standard. Most importantly, the author uses the facial motion capture technology to obtain the dynamic lip viseme feature data, during the stop’s forming-block, continuing-block, removing-block and co-articulation with vowels in the CV structure. Through research and analysis, it is found that the distribution of lip shape change characteristics of different parts’ pronunciation is different during the stop’s forming-block. In the co-articulation with [a], the reverse effect is greater than the forward effect, which is consistent with the relevant conclusions in many languages obtained by many scholars through other experimental methods. The study also found that in the process of pronunciation, the movement of the lip physiological characteristics of each speaker is random to a certain extent, but when different speakers pronounce the same sound, they can always maintain the consistency of the change trend of the lip shape characteristics.